The effect on investor trading behaviour towards future prices on crude palm oil in Malaysia based on the El Nino event / Natasya Aqilah Mat Azim - Mat Azim, Natasya Aqilah (2019)
The investor trading behaviour is the attitude of an investors in making decision on the trading in the market. The behavioural finance theory views that investors react differently to the condition of market and in turn could impact the changes in prices such as the future prices. In the Bursa Malaysia Derivative Berhad, the crude palm oil (CPO) is one of the commodities traded in the FCPO contract. Thus, this study aims to examine the relationship between investor trading behaviour and the crude palm oil future prices in Malaysia and to further testing the effect of investor trading behaviour towards the CPO future prices, the sample study is based on the El Nino phenomenon where back in 2015-2016, the event caused harsh drought season in Southeast Asian countries in turn affecting the agricultural activities including the Palm Oil production. Through segregating the event into before, during and after the El Nino event will show a more detail look on the relationship between the investor trading behaviour and the CPO future prices in Malaysia. This study uses the time-series analysis to examine the relationship between the investor trading behaviour and the CPO future prices. The study also used the adaption of tick data and Lee and Ready algorithm to first identify the investor trading behaviour in the CPO future prices. The findings concluded that there is a significant relationship of investor trading behaviour and CPO future prices during the El Nino event and an insignificant relationship of investor trading behaviour and CPO future prices before and after El Nino whereas there is also a significant relationship between trading volume and the future prices before and after El Nino and an insignificant relationship of trading volume and CPO future prices during the El Nino event.